REALITAS MASYARAKAT INDONESIA DALAM MEDIA MASSA - Asep Soegiarto (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2013)
Abstract The mass media, not just serve as the grantor information, the amusement and social control or fourth power as a nation ( the four estate ), but also as a form of public opinion who directs and public opinion in the issues developing world. Reporters when covering an event and writing it has a tendency to subjective and biased. The problem of bias in the press is not a matter of who, or of what system, is supported. The problem is that the bias exists, and the system through which our media operates seems guaranteed to ensure that bias will continue. Journalistic product in the media is not the whole of the reality of the society but only parts of reality that described as realities. In a so-called media image. The news media in a determined by its media ownership, and other factors it has a very significant role aside from bias a journalist Key Word: Objectivity, Media Biased, Media Image